Exact solutions and Darboux transformation for the reverse space–time non-local fifth-order non-linear Schrödinger equation - Shi, Xinrui; Yang, Yunqing (Frontiers in Physics, 2023)
In this paper, the nonlocal reverse space-time fifth-order nonlinear Schrӧdinger (NLS) equation has been investigated, which is proposed by nonlocal reduction of the AKNS scattering problems. The determinant representation of N-th Darboux transformation for the nonlocal reverse space-time fifth-order NLS equation is obtained, from which some interesting nonlinear wave solutions including soliton, complexiton and rogue wave solutions are derived. Moreover, the dynamics of nonlinear wave solutions are illustrated with corresponding evolution plots, and the results show that the nonlocal fifth-order NLS equation have new different properties from the local case.